PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN LAPTOP LENOVO DI KALANGAN MAHASISWA SURABAYA DI KOTA SURABAYA - Suryani, Titik; Mulyati, Awin; Maduwinarti, Ayun (Jurnal Dinamika Administrasi Bisnis, 2017)
This study examines the '' Word Of Mouth Influence Buying Decision Against Laptop Lenovo In among Students in Surabaya City ''. The purpose of this study was to determine the effect of word of mouth on purchasing decisions of Lenovo laptops among students Surabaya in Surabaya.This research method uses a quantitative approach with purposive sampling method and technique of simple linear regression analysis to test how much influence between variable volume and variable dispersion on purchasing decisions. Data were collected through questionnaires and finding respondents who have been using Lenovo laptop. The population used is that students in Surabaya and research sites in every university in Surabaya with the number of respondents hundred in the afternoon, but this study also use indicators that already includes a variable volume and dispersion of word of mouth.R2 test results showed that the amount of volume and dispersion of word of mouth influence on purchase decisions and the rest of the amount of testing R2 is influenced by other variables not included in this study. From the F test results together it can be concluded that the volume of positive influence on purchasing decisions, while the results of the t test individually variable volume and variable dispersion produce significant and it can be concluded that the variable volume and dispersion showed positive influence on the purchasing decisions of Lenovo laptops among the students in the city Surabaya, and more dominant indicator variable is the volume of word of mouth.            It is hoped with this study, especially the laptop manufacturer Lenovo to pay more attention to the advertising strategy or publications to the general public so that more people know will be a product of Lenovo laptops more often people talk about the word of mouth is increasing. Keywords: Volume word of the mouth, Dispersion of mouth, Purchase Decision